Effect of Information and Communication Technology to Improve Vocational Skills of Students of UIN Sunan Kalijaga Yogyakarta - Istiningsih, Istiningsih (Center of Language and Cultural Studies, 2021)
Education is the primary driver of a nation's progress, as it aids in the development of strong characteristics, one of which is the improvement of student vocational skills. However, there has lately been a global epidemic, particularly Covid-19, which has disturbed global community mobility, even in the realm of higher education. Because the Indonesian government relies on technology to fund higher education, students must be proficient in information and communication technologies (ICT). This expertise is thought to have the ability to influence the development of occupational skills. The goal of this study was to see how mastering ICT affected students' vocational abilities. This study took place at Yogyakarta's Sunan Kalijaga State Islamic University. This is a quantitative research method that involves the distribution of questionnaires and the use of a Likert scale. A total of 100 students were used in this investigation. The findings revealed that mastering ICT has a positive impact on students at the State Islamic University of Yogyakarta's vocational capabilities. Students' mastery of ICT will be followed by the development of their occupational skills.